2016
DOI: 10.1371/journal.pone.0146830
|View full text |Cite
|
Sign up to set email alerts
|

Long Lasting Microvascular Tone Alteration in Rat Offspring Exposed In Utero to Maternal Hyperglycaemia

Abstract: Epidemiologic studies have demonstrated that cardiovascular risk is not only determined by conventional risk factors in adulthood, but also by early life events which may reprogram vascular function. To evaluate the effect of maternal diabetes on fetal programming of vascular tone in offspring and its evolution during adulthood, we investigated vascular reactivity of third order mesenteric arteries from diabetic mother offspring (DMO) and control mother offspring (CMO) aged 3 and 18 months. In arteries isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
1
17
2
Order By: Relevance
“…The PGI2/IP interaction stimulates G protein-coupled receptors, leading to vascular smooth muscle relaxation (45). Reduction of PGI2dependent relaxation has been reported among offspring of rats with diabetes, which was associated with a decrease in IP receptor expression level (46). Diabetic hyperglycemia also results in elevated glucose levels in fetus, causing excess fetal insulin production (hyperinsulinism) (47).…”
Section: Discussionmentioning
confidence: 99%
“…The PGI2/IP interaction stimulates G protein-coupled receptors, leading to vascular smooth muscle relaxation (45). Reduction of PGI2dependent relaxation has been reported among offspring of rats with diabetes, which was associated with a decrease in IP receptor expression level (46). Diabetic hyperglycemia also results in elevated glucose levels in fetus, causing excess fetal insulin production (hyperinsulinism) (47).…”
Section: Discussionmentioning
confidence: 99%
“…In utero exposure to adverse intrauterine environment (e.g., by maternal malnutrition, obesity, toxin exposure, or diabetes) during the critical period of embryogenesis could significantly affect adult phenotype of offspring, [3][4][5]36,37 known as fetal programming. 38 In particular, the effects of in utero exposure to maternal diabetes on offspring health are under intensive inspection because the number of diabetic female at childbearing age is overwhelmingly increasing.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy complicated by diabetes is gaining attention as the number of childbearing women with diabetes is mounting due to the childhood obesity epidemic . Experimental and human studies indicate that in utero exposure to maternal diabetes not only predisposes the fetus to adverse outcomes including macrosomia, stillbirth, intrauterine growth restriction, and congenital malformations, but also increases the risk of major diseases in the adult offspring including metabolic disorders, renal dysfunction, hypertension, and vascular dysfunction . Notably, a recent human study demonstrated that adolescent offspring of diabetic mothers presented significantly higher cardiosympathetic reactivity to laboratory stressors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of elevated tone in arteries from young and aged PMCA1 Ht mice, compared to age‐matched WT animals, is consistent with the notion that PMCA1 may contribute to the development and maintenance of hypertension. Herein, we show a small reduction in the magnitude of basal tone with age, an effect which has been previously noted in mesenteric arteries and in arterioles isolated from the gastrocnemius and soleus muscles of rats (Kang et al ., ; Vessieres et al ., ). Such an age‐related change has not been associated with an elevation of BP in rats (Kang et al ., ), comparable to aging WT mice used in this study.…”
Section: Discussionmentioning
confidence: 97%